CANDIDATES OFFERED UNDERGRAD ADMISSION TO USM TO CONFIRM ACCEPTANCE OR REJECTION LATEST BY 14 AUGUST - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 12 August 2016 Candidates who have been offered a place to pursue their undergraduate degree in various programmes at Universiti Sains Malaysia (USM) have been asked to verify the acceptance or rejection of the offer the soonest possible.